Associations of accelerometer measured school- and non-school based physical activity and sedentary time with body mass index: IPEN Adolescent study - Van Dyck, Delfien; Barnett, Anthony; Cerin, Ester; Conway, Terry L; Esteban-Cornejo, Irene; Hinckson, Erica; Rubín, Lukáš; Rush, Elaine; Baron-Epel, Orna; Cain, Kelli L; Christiansen, Lars Breum; Islam, Mohammed Zakiul; et al. (The international journal of behavioral nutrition and physical activity, 2022)
BACKGROUND: This study examined the strength, shape and direction of associations of accelerometer-assessed overall, school- and non-school-based moderate-to-vigorous physical activity (MVPA) and sedentary time (ST) with BMI among adolescents across the world. Second, we examined whether these associations differed by study site and sex. METHODS: Cross-sectional data from the IPEN Adolescent study, an observational multi-country study, were used. Participants wore an accelerometer for seven days, reported height and weight, and completed a socio-demographic survey. In total, 4852 adolescents (46.6% boys), aged 11-19 years (mean age = 14.6, SD = 1.7 years) were included in the analyses, using generalized additive mixed models. RESULTS: Adolescents accumulated on average 41.3 (SD = 22.6) min/day of MVPA and 531.8 (SD = 81.1) min/day of ST, and the prevalence of overweight and obesity was 17.2% (IOTF), but these mean values differed by country. Linear negative associations of accelerometer-based MVPA and ST with standardized BMI scores and the likelihood of being overweight/obese were found. School-based ST and non-school-based MVPA were more strongly negatively associated to the outcomes than non-school based ST and school-based MVPA. Study site moderated the associations; adolescent sex did not. No curvilinear associations were found. CONCLUSIONS: This multi-country study confirmed the importance of MVPA as a potential protective factor against overweight/obesity in adolescents. Non-school-based MVPA seemed to be the main driver of these associations. Unexpected results were found for ST, calling for further examination in methodologically sound international studies but using inclinometers or pressure sensors to provide more precise ST measures.
Keywords: Accelerometry; Sedentary Behavior; Female; Overweight; akcelerometrie; ženské pohlaví; sedavý životní styl; průřezové studie; Adolescent; Obesity; lidé; cvičení; Cross-Sectional Studies; obezita; Male; nadváha; index tělesné hmotnosti; mužské pohlaví; Body Mass Index; Exercise; mladiství; Humans